Problematika Proses Peradilan Perkara Pelanggaran Ham Di Indonesia - Kumbul Kusdwidjanto Sudjadi; Yusuf Setyadi (JOURNAL OF ISLAMIC AND LAW STUDIES, 2022)
Abstract: The settlement of human rights violations in Indonesia is based on the Law on the Human Rights Court, that any person and/or group who has a strong reason that their human rights have been violated can submit reports and complaints verbally or in writing to Komnas HAM. . The law also contains provisions on the establishment of a special (ad-hoc) human rights court to try past human rights violations that occurred before the law was enacted, while a permanent human rights court only deals with crimes that occurred after the law was passed. . However, these ad-hoc courts are only established to hear special cases and are established through special procedures. The president can only establish an ad hoc court like this if there is a firm recommendation from the DPR. The process of resolving human rights violations begins with the arrest of alleged human rights violations by the investigators of the Attorney General's Office and the Public Prosecutor who are authorized to conduct detention and prosecution for the purposes of investigation and prosecution. there will be a prosecution by the attorney general or public prosecutor and an examination will be carried out in a human rights court. The weakness of the settlement of human rights violations in Indonesia based on the Law on the Human Rights Court, that the settlement of human rights violations in Indonesia is carried out in court, is by no means intended to reveal the facts of the violations that occurred, let alone to rectify history. These trials are only designed to prove whether those suspected of being most responsible for crimes against humanity or genocide are really most responsible or not. The truth that the court wants to prove is the material truth which is limited by the evidentiary procedure as regulated in the Criminal Procedure Code. Weaknesses in resolving human rights violations in Indonesia based on the Law on Human Rights Courts in the general court environment make them very dependent on the bureaucracy and administration of the general justice they occupy, there are articles that are misinterpreted so as to allow the perpetrators to be free, and there is also an age limit for both investigators and prosecutors. general public, as well as ad hoc judges, thereby preventing the entry of competent personsÂ Abstrak: Penyelesaian pelanggaran HAM di Indonesia didasarkan pada Undang-Undang Pengadilan HAM, bahwa setiap orang dan/atau kelompok yang mempunyai alasan kuat bahwa hak asasinya dilanggar dapat menyampaikan laporan dan pengaduan secara lisan atau tertulis kepada Komnas HAM. Undang-undang tersebut juga memuat ketentuan tentang pembentukan pengadilan HAM khusus (ad-hoc) untuk mengadili pelanggaran HAM masa lalu yang terjadi sebelum undang-undang tersebut diundangkan, sedangkan pengadilan HAM permanen hanya menangani kejahatan yang terjadi setelah undang-undang tersebut disahkan. Namun, pengadilan ad-hoc ini hanya dibentuk untuk mengadili kasus-kasus khusus dan dibentuk melalui prosedur-prosedur khusus. Presiden hanya bisa membentuk pengadilan ad hoc seperti ini jika ada rekomendasi tegas dari DPR. Proses penyelesaian pelanggaran HAM diawali dengan penangkapan terhadap dugaan pelanggaran HAM oleh penyidik Kejaksaan Agung dan Kejaksaan yang berwenang melakukan penahanan dan penuntutan untuk kepentingan penyidikan dan penuntutan. akan ada penuntutan oleh jaksa agung atau penuntut umum dan pemeriksaan akan dilakukan di pengadilan hak asasi manusia. Lemahnya penyelesaian pelanggaran HAM di Indonesia berdasarkan UU Pengadilan HAM, bahwa penyelesaian pelanggaran HAM di Indonesia dilakukan di pengadilan, sama sekali tidak dimaksudkan untuk mengungkap fakta pelanggaran yang terjadi. , apalagi untuk meluruskan sejarah. Pengadilan ini hanya dirancang untuk membuktikan apakah mereka yang diduga paling bertanggung jawab atas kejahatan terhadap kemanusiaan atau genosida benar-benar paling bertanggung jawab atau tidak. Kebenaran yang ingin dibuktikan oleh pengadilan adalah kebenaran materiil yang dibatasi oleh acara pembuktian sebagaimana diatur dalam KUHAP. Kelemahan dalam menyelesaikan pelanggaran HAM di Indonesia berdasarkan UU Pengadilan HAM di lingkungan peradilan umum membuat mereka sangat bergantung pada birokrasi dan administrasi peradilan umum yang mereka tempati, ada pasal-pasal yang disalahartikan sehingga memungkinkan pelakunya untuk bebas, dan juga ada batasan usia bagi penyidik dan jaksa. masyarakat umum, serta hakim ad hoc, sehingga mencegah masuknya orang-orang yang berkompeten